Representation of Racism Resistance on 12 Years a Slave Movie - Ardian Widjaja; Dr. Sunarto, M.Si (Interaksi Online, 2016)
Racism is one of the problem that will never end, from years ago that we knew as slavery era until now in the modern era where we have a lot of law that prohibit racism in the world but still based on data it’s exist. Almost the same with the current condition nowadays 12 Years a Slave is telling us about slavery era that happen in America when slavery is prohibited but in several parts of America number of slave and racism are increasing. A lot of Afro-America people is kidnapped and lost their freedom as a slave. But in the middle of this hard era of slavery so many people are fighting for their rights to be able to get a normal life and free like a normal people. The main objective of this research is to describe the resistance of Afro – American as the minority group in 12 Years a Slave movie to the racism from white people that is represented by sign both visual or linguistic in the movie. This research is a part of descriptive qualitative that is using Semiotic approach. The result of this research shown that the form of resistances are happening in so many form (closed, semi – open, and open). Started from conversation between slaves about their plan to run away, giving their opinion that explain and emphasize their opinions until their effort to run away by writing a letter that can help them to be a freeman if someone will read their letter. This movie shown how hard racism and discrimination that happen during slavery era at that time, but nothing is impossible and you can’t give up to fight for your rights and something that you suppose to get.